Ni modified Ce(Mn, Fe)O2 cermet anode for high-performance direct carbon fuel cell. (1st April 2017) - Liu, Jia; Qiao, Jinshuo; Yuan, Hong; Feng, Jie; Sui, Chao; Wang, Zhenhua; Sun, Wang; Sun, Kening
Graphical abstract: Highlights: Ni catalyst significantly improves the catalytic activity and conductivity. The reaction shemes of Ni-CMF anode is proposed. The HDCFC with Ni-CMF anode shows the maximum power density of 580.7 mW cm −2 . The HDCFC displays a good stabilty under galvanostatic operation. Abstract: Ni modified Ce0.6 Mn0.3 Fe0.1 O2 (Ni-CMF) material is evaluated as an anode material for hybrid direct carbon fuel cell (HDCFC). The Temperature Programmed Reaction (TPR) and GC test results show that the Ni additive significantly promotes the oxidation of carbon and consequently accelerates the formation rate of CO. Moreover, the Ni-CMF material is found to show a high electrical conductivity compared to pure CMF in HDCFC operating conditions. Taking advantage of the excellent catalytic activity and high conductivity, the electrolyte-supported HDCFC with Ni-CMF anode shows a high maximum power density of 580.7 mW cm −2 at 800 °C, when activated carbon is used as the fuel. Furthermore, the cell displays good stability under galvanostatic operation at current density of 50 mA cm −2 at 750 °C. These results indicate that the designed Ni-CMF composite material has the potential to be developed as an alternative anode for HDCFCs.